Performance and structural stability of Gd0.2Ce0.8O1.9 infiltrated La0.8Sr0.2MnO3 nanostructured oxygen electrodes of solid oxide electrolysis cells - Chen, Kongfa; Ai, Na; Jiang, San Ping (Elsevier Ltd, 2014)
Effect of Gd0.2Ce0.8O1.9 (GDC) infiltration on the performance and stability of La0.8Sr0.2MnO3 (LSM) oxygen electrodes on Y2O3-stabilized ZrO2 (YSZ) electrolyte has been studied in detail under solid oxide electrolysis cell (SOEC) operating conditions at 800 °C. The incorporation of GDC nanoparticles significantly enhances the electrocatalytic activity for oxygen oxidation reaction on LSM electrodes. Electrode polarization resistance of pristine LSM electrode is 8.2 Ω cm2 at 800 °C and decreases to 0.39 and 0.09 Ω cm2 after the infiltration of 0.5 and 1.5 mg cm−2 GDC, respectively. The stability of LSM oxygen electrodes under the SOEC operating conditions is also significantly increased by the GDC infiltration. A 2.0 mg cm−2 GDC infiltrated LSM electrode shows an excellent stability under the anodic current passage at 500 mA cm−2 and 800 °C for 100 h. The infiltrated GDC nanoparticles effectively shift the reaction sites from the LSM electrode/YSZ electrolyte interface to the LSM grains/GDC nanoparticle interface in the bulk of the electrode, effectively mitigating the delamination at the LSM/YSZ interface. The results demonstrate that the GDC infiltration is an effective approach to enhance the structural integrity and thus to achieve the high activity and excellent stability of LSM-based oxygen electrode under the SOEC operating conditions.